Pengaruh Gaya Hidup, Media Sosial, Literasi Keuangan dan e-Money terhadap Perilaku Konsumtif (Studi Kasus Pada Generasi Z di Kota Jambi) - Agustian, Muhamad; Setiawati, Rike; Ihsan, Moh (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to examine the influence of lifestyle, social media, financial literacy, and e-money usage on consumptive behavior. The research adopts a quantitative approach with a probability sampling technique, specifically simple random sampling. A total of 100 respondents participated, with data collected through a digital questionnaire using Google Forms and a 4-point Likert scale. Data analysis was conducted using the Partial Least Square (PLS) method with the aid of Smart PLS 4 software. The findings reveal that lifestyle, social media, and e-money have a positive and significant impact on consumptive behavior, while financial literacy has a significant negative effect.